Characterization of Narrow Band UHF Radio Propagation Channels in Tunnel Environments - Zhang yaoping Zheng guoxin Zhang wenmei Sheng jianhuan (Tongxin xuebao)
Propagation measurements taken in five tunnels at 900 and 1800 MHz for microcellular and personal communication are presented.The power distance factors to characterize propagation loss in straight empty tunnel section are given.The effects of pedestrians,vehicle,and curvature on propagation are also investigated.Furthermore,it is found that The log normal distribution basically fits the slow variation of the received signals.Whereas the Racian distribution closely models the fast fading in the straight empty sections of the tunnels,however,the Rayleigh distribution does not fit the fast fading in the curved section of the tunnels as well as expected.